ปัจจัยที่มีผลต่อความต้องการของผู้ประกอบการร้านกาแฟในอำเภอเมืองเชียงใหม่ในการซื้อเมล็ดกาแฟออร์แกนิค - นิภาวรรณ จันทร์ตา (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2018)
This independent study aimed to examine factors affecting demand of coffee shop owners in Mueang Chiang Mai district towards buying organic coffee beans. Samples of the study were specified to 100 fresh coffee shop owners in Mueang Chiang Mai district and questionnaires were used as the tool. Data analysis was conducted by the use of descriptive statistics, including frequency, percentage, and means, as well as inferential statistics, consisting of Chi-square Test and analysis of variance: ANOVA. The findings revealed that most respondents were female in the age of 21-39 years old. They were the owner of the coffee shop with 1-3 employees. The main target consumer was a group of students. Beside coffee, the beverage that they served customers was tea. Type of coffee shop that the majority owned was the coffee corner and snack bar type; followed by the coffee-corner type. The studied results indicated that 56% of respondents did not want organic coffee beans because there was a limited number of organic coffee consumers or the maker base was too narrow. In addition, the consumers agreed that there was no necessary for the coffee shop to use the organic coffee beans. However, 44% of respondents indicated that they would serve organic coffee to consumers. Hereafter was shown their top 3 reasons of buying it: to add product value, to pay attention to consumer’ health, and to present good things for consumers as the organic coffee beans were safe and non-toxic. The findings also presented that for the consumers who bought roasted organic coffee, all of them preferred the organic coffee beans, especially Arabica coffee, produced in Thailand, particularly at Doi Saket and Chiang Dao mountain areas. The respondents noticed that price of organic coffee beans from Thailand was about 501-1,000 Baht/kilogram and expected to use 4-6 kilograms/month. Their considerations were highly paid to the reliability of the manufacturer and the certifications from reliable institutes, which were the certificate of “Organic Thailand” and the “Good Agriculture Practices: GAP”, as certified by the Department of Agriculture, respectively. Before making buying decision, they tested it by themselves and collected data from the roasted coffee bean traders. They learned about the organic coffee beans from sales representatives and friends, respectively. The tope 3 places where they bought the organic coffee beans were the roasted coffee bean companies or factories, the manufacturers or cooperatives of roasted coffee beans, and modern trade, accordingly. The results of the study on marketing mix factors showed that the following factors affected demand of the respondents towards buying organic coffee beans at high level: product, place, price, and promotion, respectively according to mean values. The top 10 sub-factors that were rated at the highest level included the taste of roasted organic coffee beans, the consistency potency of organic coffee beans, the quality of roasted organic coffee beans, the freshness of roasted organic coffee beans, the reasonable price comparing to its quality, the good package to prevent coffee beans from humidity and oxygen, the convenient and easy-to-access place to buy the product, the clear price tag, the sufficient amount of stocks to serve customer needs, the variety channels to make orders such as telephone, website, and e-mail, the fast services from the officers, the availability of product delivery, and the availability of preferred coffee breeds. According to an analysis on differences of marketing mix factors among 4 types of coffee shops: coffee corner, coffee corner and snack bar, quick restaurant, and booth or small shop, the results presented that the owners of all types of coffee shop paid concern on the factors namely product, price, place, and promotion in an account that these factors affected the purchase of organic coffee beans, indifferently. However, the differences were found in following sub-factors: sources of the organic coffee beans from the highland in the North, warehouses, activity arrangement such as training workshop for coffee shop, and having new products to be introduced regularly.